Kualitas Dan Makna Hadis Penggunaan Parfum - Siti Sadiah; Anisatun Muthi’ah; Wasman Wasman (IAIN Syekh Nurjati Cirebon, 2021)
This research is motivated by the debate about the use of perfume in women. History states that if women use perfume, they are included in the category of adulterers. On the other hand, the use of perfume is a suggestion of the Prophet Muhammad. The purpose of this study is to examine the quality and meaning contained in the traditions of the use of perfume. This type of research is library research (library) which is processed by descriptive analysis method. The results of the study indicate that the hadith recommending the use of perfume from the history of Tirmizi is of da'if quality and the history of Ahmad bin Hambal is of the quality of hasan li-zatihi. Hadiths prohibiting the use of perfume, both the history of Abu Dawud, Tirmizi, Nasa'i, Ahmad bin Hambal, and Darimi are of hasan li-zatihi quality. The meaning contained is that women may use perfume on conditions in accordance with the applicable provisions in terms of type and context. The prohibition on the use of perfume applies if its use is excessive and there is an element of intent to attract attention around.